The new manufacturing challenge : - Suzaki, Kiyoshi (Free Press,Collier Macmillan Publishers, 1987)
Maintaining world competitiveness has been the clarion call for many industries in the 1980s. For manufacturing companies, improving production efficiency has been the key. This work lays out specific suggestions for improving manufacturing techniques on the shop floor. The chapters, profusely illustrated, treat topics such as quick setup, job rotation, U-shaped production lines, and preventive maintenance. In each, the author uses his diverse experience as an efficiency expert for several leading consulting houses to good advantage. However, the volume lacks a strong philosophical framework and comes off rather like a dry list of helpful hints. Recommended only for production specialists. Gene R. Laczniak, Coll. of Business Administration, Marquette Univ., Milwaukee